Empowerment of the Graduates through an Entrepreneurial Approach in the Educational Curriculum - Eukael N. Mbuyisa; Blessed Mveku; Tanaka T.T. Mutero; Esnath T. R Manhiwa (IJIRD, 2022)
This study aimed to evaluate the empowerment of the graduates through an entrepreneurial approach in the educational curriculum. The study was conducted from December 2021 to March 2022 and is based on information collected from both primary and secondary sources. The sample for this study is taken from lecturers and students at Midlands State University, Zimbabwe. The study adopted a simple random sampling technique to select a sample of 200 respondents. The students distributed two hundred questionnaires, but only 195 were returned. Primary data were collected using questionnaires and interviews. Collected data were analyzed and presented in the form of tables, pie charts, and graphs. Findings of this study revealed that the study found that opportunity recognition, independence, and pitching of business ideas were the top items in the module content that inspired the intention to start an enterprise among undergraduate students. The study adds value to curriculum development by identifying entrepreneurship course content that increases the desire to be independent and shifts students' focus from a job seeker to a career and enterprise development orientation. Therefore, practical activities are recommended for stimulating entrepreneurial intentions among students rather than theoretical learning approaches such as telling success stories and sharing videos. The study was limited in that it included respondents from Midlands State University.